Schwannoma: A Rare Hoffa's Fat Pad Tumor - Caballero Martel, Jonathan Ruben; Estévez Sarmiento, Sara (The Surgery Journal, 2019)
Hoffa's fat pad can be affected by a variety of tumors. Schwannomas are benign and typically solitary neoplasms of the peripheral nerve sheath; they are made up of the neoplastic Schwann cells and are usually located eccentrically. Malignant schwannomas are extremely uncommon. Here we report a case of an intra-articular schwannoma of the knee. A 54-year-old man presented with a painful lump in the medial aspect of the knee. Magnetic resonance imaging revealed a well-circumscribed intra-articular mass, which was later diagnosed as an intra-articular schwannoma based on biopsy findings.
Keywords: schwannoma; intra-articular tumor; knee joint schwannoma